Solar Energy Engineering: Processes and Systems - Kalogirou, Soteris A. (My University, 2013)
Energy policy promoting sustainable development is transforming global energy markets. Solar power, the most abundant of all renewable resources, is crucial to greater achieving energy security and sustainability. This new edition of Solar Energy Engineering: Processes and Systems from Prof. Soteris Kalogirou, a renowned expert with over thirty years of experience in renewable energy systems and applications, includes revised and updated chapters on all areas of solar energy engineering from the fundamentals to the highest level of current research. The book includes high interest topics such as solar collectors, solar water heating, solar space heating and cooling, industrial process heat, solar desalination, photovoltaic technology, solar thermal power systems, modeling of solar energy systems and includes a new chapter on wind energy systems. As solar energy's vast potential environmental and socioeconomic benefits are broadly recognized, the second edition of Solar Energy Engineering: Processes and Systems will provide professionals and students with a resource on the basic principles and applications of solar energy systems and processes and can be used as a reference guide to practicing engineers who want to understand how solar systems operate and how to design the systems.
Keywords: Solar energy; Engineering; Energy systems